On Ontological Functors of Lesniewski's Elementary Ontology - Urbaniak, Rafal (Reports on Mathematical Logic, 2006)
We present an algorithm which allows to define any possible sentence-formative functor of Leśniewski's Elemen- tary Ontology (LEO), arguments of which belong to the category of names. Other results are: a recursive method of listing possible functors, a method of indicating the number of possible n-place ontological functors, and a sketch of a proof that LEO is function- ally complete with respect to {∧,¬, ∀, ε}